Biomacromolecular charge chirality detected using chiral plasmonic nanostructures. Issue 2 (18th October 2019) - Rodier, Marion; Keijzer, Chantal; Milner, Joel; Karimullah, Affar S.; Roszak, Aleksander W.; Barron, Laurence D.; Gadegaard, Nikolaj; Lapthorn, Adrian J.; Kadodwala, Malcolm
Abstract : The charge distributions of solvent exposed surfaces of complex biomolecules such has proteins are unique fingerprints. Abstract : The charge distributions of solvent exposed surfaces of complex biomolecules such has proteins are unique fingerprints. The chirality of these charge distributions result in stereo-specific electrostatic interactions which help define how proteins interact with each other, contributing to specificity in protein–protein interactions. Thus it is a key concept in understanding chemical processes in biology. There is currently no known spectroscopic phenomenon that allows rapid characterisation of chiral surface charge distributions. We show that this essential property that is currently "invisible" to optical spectroscopy, can be detected by monitoring asymmetries in the chiroptical response of protein–plasmonic nanostructure complexes. The unique capabilities of the phenomenon are utilised to discriminate between a structurally homologous series of proteins, type II dehydroquinase (DHQase) derived from different organisms. The proteins are indistinguishable with conventional structurally sensitive spectroscopy ( i.e. circular dichroism). We show that discrimination between proteins can be achieved by detecting differences in chiral surface charge distributions. The phenomenon is explained with a simple model whereby the chiroptical properties of the plasmonic structures are perturbed by the induction of an enantiomeric mirror image charge distribution of the protein in the metal. This new phenomenon has broad impact, it is a powerful tool for discriminating between structurally homologous biomaterials, but will also provide information relevant to macromolecular interactions.